The relationship of self-concept with other variables of Hansenite High School students - Teng, Judith M. (Judith Monroid) 1947-
The objectives of this study were to determine the extent of the relationship between self-concept and personality make-up, self concept and academic achievement, self-concept and mental ability, self-concept and physical condition. The study further tackles the difference between self-concept of the hansenite and non-hansenite high school students enrolled for the school year 1981-1982.